The Challenges of European Public Health Surveillance Systems - An Overview of the HIV-AIDS Surveillance - Oliveira, Alexandra (2019)
Surveillance has been defined as the continual scrutiny of all aspects in emerging and the spread of a disease that is pertinent to effective control, involving a systematic collection, analysis, interpretation, and dissemination of health data. Given their fragmentation several problems inherent to data must be recognized. This paper aims to provide an overview of European Public Health Surveillance Systems emphasizing their structure and main challenges. The HIV-AIDS surveillance is overview as a particular case. The most common issues are unrepresentativeness, changes in the implementation through time, inconsistent use of case definitions, miss diagnoses, miss or fail to report a case, reporting delay, and errors during completion of the form or data entry. The HIV - AIDS surveillance is one of the most complex mainly due to the special epidemiology of the disease surrounding the transmission modes and the lack of treatment and all the socio-ecological framework involved.